2013
DOI: 10.1093/jncimonographs/lgt033
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Expression: How Providing Emotional Support Online Improves Cancer Patients’ Coping Strategies

Abstract: There is increasing importance for scholars to distinguish the effects of expression from reception to understand the processes involved in producing psychosocial benefits. This study shows that emotional support is more than something cancer patients receive; it is part of an active, complex process that can be facilitated by social media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…The mixed findings regarding the effectiveness of communicating MERSrelated information might stem from the difference in attributes between message expression and reception. In an online communication environment, the expression of messages is a self-involved and goal-directed behavior, since composing messages and reflecting on them are cognitively demanding activities (Namkoong et al, 2013). SNSs continue to grow in popularity as sites for users to share information about their thoughts and activities (Vitak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixed findings regarding the effectiveness of communicating MERSrelated information might stem from the difference in attributes between message expression and reception. In an online communication environment, the expression of messages is a self-involved and goal-directed behavior, since composing messages and reflecting on them are cognitively demanding activities (Namkoong et al, 2013). SNSs continue to grow in popularity as sites for users to share information about their thoughts and activities (Vitak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research provides evidence that social media are very effective in reinforcing or changing attitudes and behaviors in a crisis. For instance, Mou and Lin (2014) examined whether the public's use of social media was related to any forms of prevention action in relation to food safety in China. Their findings showed that the use of microblog or Weibo in China was positively associated with public awareness of a series of food safety incidents and factual awareness, in addition to preventive actions regarding food risks.…”
Section: Linking Sns Communication To Cognitive Characteristics and Pmentioning
confidence: 99%
“…Such perception in turn predicted greater perceived peer smoking norms, resulting in more positive attitudes toward smoking and greater smoking intentions. In an online communication environment, the expression of messages is a self-involved and goal-directed behavior (Namkoong et al, 2013; Yoo, Choi, & Park, 2016). Thus, social media users who talk about smoking might already have preexisting attitudes toward smoking.…”
Section: Discussionmentioning
confidence: 99%
“…A recent intervention study found that expressing social support was associated with perceived bonding within the social media group and positive coping strategies, whereas receipt alone of supportive messages was not. 27 …”
Section: Key Principles Of Social Media To Enhance Cancer Prevention mentioning
confidence: 99%